«Queen of sports» On the way to the XXXIII Olympic Games in Paris - Mirzoev, O. M.; Kalinina, O. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the performances of the strongest athletes and sports teams following the results of the 2022 and 2023 World Championships.